The relationship between federal tax installments and the future profitability of Brazilian companies listed on B3 S/A - Bonetti, Brigitti Brunocilla; Theiss, Viviane; Dalcero, Kátia (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: The objective of this study is to ascertain whether federal tax installments exert an influence on the future profitability of companies listed on B3 S/A. Methodology: The sample comprises 129 non-financial Brazilian companies listed on the Brasil Bolsa Balcão (B3 S/A) from 2018 to 2022. To achieve the study's objective of ascertaining the relationship between tax installments and future profitability, two distinct profitability measures were employed: The variables of interest return on assets (ROA) and earnings before interest, taxes, depreciation, and amortization (EBITDA). The ordinary least squares (OLS) regression model was employed to test the formulated hypotheses and analyze the data, with robust standard errors. Results: The results indicate that tax installments exert a significant influence on the future profitability of these companies. In light of these findings, it can be concluded that companies employ tax installments as a means of indirect financing, with the objective of enhancing economic benefits and the financing of their operations. This approach has a positive impact on profitability and the generation of future cash flows. Contributions of the Study: The study makes a contribution to the existing literature by identifying how companies use tax installment options for their indirect financing and increase in profitability rates. It also highlights the influence of federal tax installments on increasing the future profitability of Brazilian companies. In terms of practical and social contributions, the results provide mechanisms for discussion on the application of tax laws and for social discussions on the impact of taxes on business performance.